(untitled) (Journal of Kidney Cancer, 2023)
This retrospective study aims to describe the characteristics of renal cell carcinoma (RCC) in Saudi Arabia, in terms of epidemiology, clinical presentation, tumor subtype, Fuhrman grade, tumor size and stage, and overall survival. A total of 431 adult patients with a histopathological diagnosis of RCC between 2015 and 2023 were included in the analysis. Most patients (72.4%) had clear cell tumors, followed by chromophobe (15.1%) and papillary (12.5%) subtypes. In males, papillary RCC (85.2%) was more common compared to clear cell (59.8%) and chromophobe (67.7%) subtypes. Significant differences were observed in median body mass index (BMI) across tumor subtypes, and papillary tumor patients exhibited the highest incidence of hematuria (33.3%) compared to other subtypes. The Fuhrman grade also varied significantly among RCC types. Survival times were found to be lower for patients with papillary tumors. No significant difference was observed based on patients’ nationality. This study can inform clinical decision-making on patient prognosis and management as well as public health efforts aimed at reducing the alarming rise of RCC incidence.